A target localization error analysis method for bistatic SAR based on gradient theory. Issue 5 (4th May 2019) - Wu, Junjie; Du, Ning; Xu, Yushi; Li, Zhongyu; Yang, Jianyu
ABSTRACT: Bistatic range sum (BRS) equation and Doppler equation of bistatic synthetic aperture radar (BiSAR) can be used to achieve target localization in BiSAR images. Because of the double square roots existing in BiSAR range history, it is hard to analyze the target localization error of a BiSAR system by calculating the partial derivatives directly. In this letter, a method utilizing spatial gradient vectors of BRS and Doppler frequency is proposed to derive the analytic solution of localization error for BiSAR. The effectiveness of the method is validated by a numerical simulation experiment.